A Lenape among the Quakers : the life of Hannah Freeman - Marsh, Dawn G. (University of Nebraska Press, 2014)
On July 28, 1797, an elderly Lenape woman stood before the newly appointed almsman of Pennsylvania's Chester County and delivered a brief account of her life. In a sad irony, Hannah Freeman was establishing her residency-a claim that paved the way for her removal to the poorhouse. Ultimately, however, it meant the final removal from the ancestral land she had so tenaciously maintained. Thus was William Penn's "peaceable kingdom" preserved. A Lenape among the Quakers reconstructs Hannah Freeman's history, traveling from the days of her grandmothers before European settleme